3-Year effect of weight loss via severe versus moderate energy restriction on body composition among postmenopausal women with obesity - the TEMPO Diet Trial. Issue 6 (June 2020) - Seimon, Radhika V.; Wild-Taylor, Anthony L.; McClintock, Sally; Harper, Claudia; Gibson, Alice A.; Johnson, Nathan A.; Fernando, Hamish A.; Markovic, Tania P.; Center, Jacqueline R.; Franklin, Janet; Liu, Peter Y.; Grieve, Stuart M.; et al.
Abstract: We have previously shown that a severely energy-restricted diet leads to greater loss of weight, fat, lean mass and bone mineral density (BMD) at 12 months in postmenopausal women with obesity than a moderately energy-restricted diet. We now aim to evaluate whether these effects are sustained longer term (ie, at 36 months). 101 postmenopausal women were randomized to either 12 months of moderate (25 to 35%) energy restriction with a food-based diet (moderate intervention), or 4 months of severe (65 to 75%) energy restriction with a total meal replacement diet followed by moderate energy restriction for 8 months (severe intervention). Body weight and composition were measured at 0, 24 and 36 months. Participants in the severe intervention lost 1.5 to 1.7 times as much weight, waist circumference, whole-body fat mass and visceral adipose tissue compared to those in the moderate intervention, and were 2.6 times more likely (42% versus 16%) to have lost 10% or more of their initial body weight at 36 months ( P < 0.01 for all). However, those in the severe versus moderate intervention lost 1.4 times as much whole-body lean mass ( P < 0.01), albeit this was proportional to total weight lost and there was no greater loss of handgrip strength, and they also lost 2 times as much total hip BMD between 0 and 36 months ( P < 0.05), with this bone loss occurring in the first 12 months. Thus, severe energy restriction is more effective than moderate energy restriction for reducing weight and adiposity in postmenopausal women in the long term (3 years), but attention to BMD loss in the first year is required. Trial registration: Australian New Zealand Clinical Trials Registry Reference Number: 12612000651886, anzctr.org.au. Abstract : Nutrition; Diet; Musculoskeletal System; Endocrinology; Clinical Research; weight loss; Body composition; diet-reducing; Obesity; Magnetic Resonance Imaging.